Genetic polymorphism of thiopurine methyltransferase and thiopurine therapy: from molecular genetics to clinical medicine - Evans, William (Henry Stewart Talks, 2009)
Pharmacogenomics to optimize cancer chemotherapeutics, The genetic polymorphism of thiopurine methyltransferase (TPMT), Its influence on thiopurine (e.g., mercaptopurine, azathioprine) therapy, Molecular and biochemical basis of this pharmacogenetic trait, Clinical diagnostic widely used to individualize and optimize thiopurine therapy for cancer and other diseases, Update talk: Hematologic toxicity of thiopurines, Update talk: TPMT, Update talk: NUDT15, Update talk: Ancestry-related differences in allele frequency
Updated at 2022/08/30